Primary mediastinal seminoma - Medeiros, Cleverson Winston de Liz (2002)
The primary mediastinal seminoma is a rare disease, mainly in women. There are only eight cases of seminoma described in the English literature. The disease has a greater incidence in the third and fourth decades of life. An important characteristic is the radio sensibility of the tumor, while cisplatin or carboplatin based chemotherapy is applied for advanced disease. The authors describe a 76-year-old female patient with mediastinal seminoma. Her first symptoms were chest pain, cough with sputum and dyspnea in median efforts. Image exams and thoracotomy performed her diagnostic, added to characteristic alterations in the germ cell tumor-markers. Cisplatin was the proposed treatment, but she had a severe respiratory failure and died. The authors review the incidence, pathogenesis, diagnosis, treatments to the mediastinal seminoma and a prognostic classification proposed by International Germ Cell Cancer Collaborative Group.